Vision Impairment and Associated Factors in a Coastal Province of Southern China: The Fujian Eye Study - Li, Yang; Hu, Qinrui; Li, Xiaoxin; Hu, Yonghua; Qin, Xueying; Wang, Bin; Ren, Tao (Frontiers in Photonics, 2022)
Purpose To evaluate prevalence and correlations of vision impairment (VI) among urban and rural adults in a coastal province of Southern China. Design population-based cross-sectional study Methods The study was designed to recruit residents aged over 50 years in randomly sampled communities of Fujian Province from May 2018 to October 2019. Participants underwent a questionnaire about socioeconomic and biological factors and physical and visual examinations. And best corrected visual acuity (BCVA) were measured for the participants to assess VI.VI was defined as best corrected visual acuity (BCVA) in better eyes of 20/60 or worse, blindness as BCVA in better eyes worse than 20/400. Results 6823 participants were included in this report. VI prevalence (5.08% vs 2.79%, P<0.001) was higher in inland populations, compared with coastal populations, while there was no significantly difference (2.97% vs 3.73%, P=0.082) between urban populations and rural populations. VI was significantly correlated with biological and sociodemographic factors, including age, educational background, income and refractive error. Sex and urbanization were not statistically significantly associated with VI. Conclusions High prevalence of VI in southeast China suggested more need for increasing accessible services and favorable policy for enhancing eye health on rural and inland elderly.